Efficacy of permanent wildlife fences as barriers to amphibian movement - Conan, Antonin; Le Brishoual, Meven; Garnier, Lorène; Fleitz, Julie; Dehaut, Nathan; Enstipp, Manfred; Jumeau, Jonathan; Handrich, Yves (Frontiers in Ecology and Evolution, 2023)
To mitigate habitat fragmentation and roadkill, roads are increasingly equipped with wildlife fences and underpasses. However, the effectiveness of such fences in preventing road access for amphibians has not been tested under controlled conditions. In 2019 and 2020, we tested the efficacy of full panel fences of differing material, height, and shape (presence/absence of an overhang), to prevent road access for adult and juvenile amphibians. We selected five species according to locomotion mode: Natterjack toads (runners), European green toads (short-distance jumpers), agile frogs (proficient jumpers), American tree frogs (proficient climbers) and smooth newts (climbers). We found that Natterjack and green toads were unable to cross a concrete fence with a height of 13 and 24 cm, respectively. Addition of a 10 cm overhang reduced the height required to prevent crossing further to 10 and 17 cm, respectively. The ability of these less agile species to cross a certain fence height depended on body length. By contrast, jumping agile frogs and climbing tree frogs were not stopped by the greatest fence height tested (40 cm). However, addition of the overhang stopped the climbing tree frogs at a concrete fence height of 35 cm. An alternative metal fence (with overhang) was tested with some species and performed similar to the concrete fence (with overhang). Finally, the greatest concrete fence height passed by climbing juveniles was 20 cm (smooth newts). Hence, to stop amphibians from road crossing, we recommend the construction of durable (concrete or galvanized metal) and well-maintained fences with a minimum height of 40 cm with a 10 cm overhang.